PENTAQUARK 04 : Proceedings of the International Workshop, SPring-8, Japan, 20-23 July 2004 - Hosaka, Atsushi; Hotta, Tomoaki (World Scientific, 2005)
The papers collected in this book represent an exciting contribution to the growing body of experimental and theoretical research into exotic hadrons. The prime focus of the volume is the latest work on pentaquark baryons. The in-depth experimental reports cover both positive and negative evidence for the existence of various combinations of particles, and photo-electro production, hadronic production and high-energy processes are discussed in detail. Important theoretical areas of current interest are considered, including chiral solitons, constituent quarks, the QCD sum rule, lattice QCD, pr.